(untitled) (Progressive Agriculture, 2017)
An experiment was conducted using a randomized complete block design to explore the performance of rice landraces under salinity stress condition at Plant Breeding Division, Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh. The experiment was consisted of five replication and three different salt treatments viz., EC-6 dSm-1, EC-8 dSm-1, EC-12 dSm-1 with one control condition. Analysis of variance for yield and yield contributing traits showed significant (p<0.01) variation among the genotypes. The performance of all the landraces with respect to yield and yield contributing traits differed from each other under saline condition. Hogla, TalMugur, Nona Bokhra were identified as tolerant to salinity compared to check Binadhan-8, Binadhan-10 and BRRI dhan47 at 12 dSm-1 salinity treatment. All the traits under this study reduced in the salt stress except days to 50% flowering. In higher salt stress landrace Tal Mugur showed maximum yield followed by Ghunshi and Hogla. The findings of this study can be used for further study and also for developing salt tolerant rice varieties. Progressive Agriculture 28 (1): 1-6, 2017